Differentiation of Parkinson's disease and atypical parkinsonian syndromes by transcranial ultrasound. Issue 3 (16th February 2005) - Behnke, S; Berg, D; Naumann, M; Becker, G
Abstract : Neuroimaging is known to complement clinical findings in the diagnostic work up of parkinsonian syndromes. Recently, transcranial ultrasound was reported to have a high diagnostic yield in differentiating idiopathic Parkinson's disease (IPD) from atypical parkinsonian syndromes. This report summarises the sonographic findings of 102 patients with IPD, 34 patients with multiple system atrophy, and 21 patients with progressive supranuclear palsy. Increased echogenicity of the substantia nigra is predictive for IPD whereas a low echogenic substantia nigra, particularly when combined with a hyperechogenic lentiform nucleus, strongly suggests an atypical Parkinsonian syndrome. The underlying causes for the differential echo pattern of the substantia nigra remain unknown.